2009
DOI: 10.1007/s00383-009-2391-1
|View full text |Cite
|
Sign up to set email alerts
|

Colon replacement of vagina to restore menstrual function in 11 adolescent girls with vaginal or cervicovaginal agenesis

Abstract: This group of patients forms a separate subgroup needing a conduit not only for sexual function but also for menstruation. However, if treated by the method described herein, they should be cautioned against pregnancy if they have cervicovaginal agenesis and against vaginal delivery if they have vaginal agenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 18 publications
4
28
0
1
Order By: Relevance
“…These include excessive mucosal discharge, bowel obstruction, anastomotic leaks, bladder/ureteral injury, stenosis, prolapse, polyp formation, diversion colitis, ulcerative colitis and rarely malignancy [1,15]. Despite these complications, several authors have reported successful bowel vaginoplasties [1,2,4,15,16]. Clearly, the multiplicity of procedures for this complex anomaly indicates that there is no perfect solution.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These include excessive mucosal discharge, bowel obstruction, anastomotic leaks, bladder/ureteral injury, stenosis, prolapse, polyp formation, diversion colitis, ulcerative colitis and rarely malignancy [1,15]. Despite these complications, several authors have reported successful bowel vaginoplasties [1,2,4,15,16]. Clearly, the multiplicity of procedures for this complex anomaly indicates that there is no perfect solution.…”
Section: Discussionmentioning
confidence: 99%
“…Further, ours is a conservative society where the loss of the vagina and fertility makes it very unlikely for the patient to get married [19]. The utero-coloneovaginoplasty, described earlier by Kanniayan and Sen, is tailored to meet this need-ensuring a safe, wide, epithelially lined, lubricated conduit for menses and coitus, at the cost of infertility [4]. The wide anastomosis provides free drainage of the menstrual blood, thus preventing haematometra and pyometra [4,19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations